Nine weeks versus 1 year adjuvant trastuzumab in combination with chemotherapy: final results of the phase III randomized Short-HER study‡. (13th September 2018) - Conte, P; Frassoldati, A; Bisagni, G; Brandes, A A; Donadio, M; Garrone, O; Piacentini, F; Cavanna, L; Giotta, F; Aieta, M; Gebbia, V; Molino, A; et al.
Abstract: Background: Chemotherapy plus 1-year trastuzumab is the standard adjuvant treatment of HER2-positive breast cancer. The efficacy of less extended trastuzumab exposure is under investigation. The short-HER study was aimed to assess the non-inferiority of 9 weeks versus 1 year of adjuvant trastuzumab combined with chemotherapy. Patients and methods: HER2-positive breast cancer patients with node-positive or, if node negative, with at least one risk factor (pT>2 cm, G3, lympho-vascular invasion, Ki-67 > 20%, age ≤35 years, or hormone receptor negativity) were randomly assigned to receive sequential anthracycline–taxane combinations plus 1-year trastuzumab (arm A, long) or plus 9 weeks trastuzumab (arm B, short). This study was designed as a non-inferiority trial with disease-free survival (DFS) as primary end point. A DFS hazard ratio (HR) <1.29 was chosen as the non-inferiority margin. Analyses according to the frequentist and Bayesian approach were planned. Secondary end points included 2-year failure rate and cardiac safety. Results: A total of 1254 patients from 82 centers were randomized (arm A, long: n = 627; arm B, short: n = 626). Five-year DFS is 88% in the long and 85% in the short arm. The HR is 1.13 (90% CI 0.89–1.42), with the upper limit of the CI crossing the non-inferiority margin. According to the Bayesian analysis, the probability that the short arm is non-inferior to the long one is 80%. The 5-year overall survival (OS) is 95.2% in the long and 95.0% in the short arm (HR 1.07, 90% CI 0.74–1.56). Cardiac events are significantly lower in the short arm (risk-ratio 0.33, 95% CI 0.22–0.50, P < 0.0001). Conclusions: This study failed to show the non-inferiority of a shorter trastuzumab administration. One-year trastuzumab remains the standard. However, a 9-week administration decreases the risk of severe cardiac toxicity and can be an option for patients with cardiac events during treatment and for those with a low risk of relapse. Trial Registration: EUDRACT number: 2007-004326-25; NCI ClinicalTrials.gov number: NCT00629278.